Patient Perceptions of Unmet Medical Need in Rheumatoid Arthritis: A Cross-Sectional Survey in the USA - Christine Radawski; Mark C. Genovese; Brett Hauber; W. Benjamin Nowell; Kelly Hollis; Carol L. Gaich; Amy M. DeLozier; Kelly Gavigan; Maria Reynolds; Anabela Cardoso; Jeffrey R. Curtis (Rheumatology and Therapy, 2019)
Abstract Introduction Many rheumatoid arthritis (RA) patients do not achieve their treatment goals and experience symptoms that affect psychosocial outcomes and daily activities. This study aimed to identify and quantify the unmet needs perceived by US patients with RA currently taking a disease-modifying antirheumatic drug (DMARD). Methods A cross-sectional, web-based survey was conducted with RA patients recruited through CreakyJoints, an online patient support community, and ArthritisPower®, an online patient research registry, from December 2017 to January 2018. Participant patients were aged ≥ 21 years, failed ≥ 1 DMARDs, and were receiving their current DMARD(s) for ≥ 6 months; they answered 50 questions about treatment history, RA symptoms, and flares and completed the Rheumatoid Arthritis Impact of Disease (RAID) questionnaire and the Treatment Satisfaction Questionnaire for Medication (TSQM). Treatment satisfaction was defined by a TSQM global satisfaction score ≥ 80. Results Of 415 patients screened, 258 (62%) were eligible and completed the survey; 87% were women, and 87% white, with mean (SD) age of 54.5 (11.4) years. A total of 232 patients (90%) had current or past biologic DMARD (bDMARD) use, with 67% currently on a bDMARD, 65% on ≥ 1 conventional synthetic DMARD, and 40% on methotrexate. Forty-three percent of patients reported daily/almost daily use of prescription pain medications, and 44% reported a current flare. Mean (SD) TSQM scores were 59 [20] for effectiveness, 59 [26] for side effects, 72 [18] for convenience, and 65 [21] for global satisfaction. The mean (SD) RAID overall score was 5.1 (2.0) on a 0–10 scale. Only 26% (67 patients) were satisfied with their RA treatment. Patients not satisfied with treatment reported higher RAID scores overall and by domain, and approximately half reported a current flare. Conclusions Results from this real-world survey suggest that three-fourths of RA patients are not satisfied with treatments, which include bDMARDs. Patients continued to experience bothersome symptoms that impacted their daily activities and life. There remains a need for improved disease management among currently treated RA patients. Funding Eli Lilly and Company (Indianapolis, IN, USA).